Ru/graphene hybrid film catalyst for NaBH4 hydrolysis reaction - Megersa, Daba Deme; Kim, Youngho; Kim, Noeul; Lee, Jaeyeong; Bae, Jong Seong; Choi, Jae Young; Yu, Hak Ki (International Journal of Hydrogen Energy, 2022)
In this study, a thermal release tape-supported Ru on graphene film (Ru/G/TRT) was proposed as a catalyst for the dehydrogenation of sodium borohydride (NaBH4). A 200-nm-thick Ru film deposited on the C-plane of sapphire by physical vapor deposition was used for the synthesis of graphene via chemical vapor deposition. X-ray diffraction analysis revealed the polycrystalline nature of the thin films. Furthermore, Raman spectroscopy and scanning electron microscopy revealed the successful synthesis of graphene. Thus, the prepared Ru graphene (Ru/G) structure was covered with TRT, while simultaneous etching resulted in a Ru/G/TRT structure. The water displacement method was employed to evaluate the catalytic performance of the proposed structure, which was found to highly improve with respect to the etched Ru/G structure, with maintenance of stability after repeated use. Finally, surface study by X-ray photoelectron spectroscopy revealed the presence of metallic Ru on both Ru/G and Ru/G/TRT surfaces after repeated use, which further confirmed the stability of the structure.
Keywords: Graphene films; Hybrid film; Hydrolysis reaction; Physical vapour deposition; Ru catalysts; Ru film; Sodium boro hydrides; Sodium borohydrides; Thermal release; ]+ catalyst; Dehydrogenation; Graphene; NaBH4; Ru catalyst